God the Logos. Exegetical Sketches on the Johannine Prologue (1:1–18) - N. Glubokovsky, N. (Forum Theologicum Sardicense, 2025)
N. N. Glubokovsky, God the Logos. Exegetical sketches on the Johannine prologue (1:1–18). The study explores the Orthodox Christian perspective on the Prologue of the Gospel of John. Keywords: Biblical Exegesis, Gospel of John, Orthodox Christianity, Biblical Studies